Study of Heterogeneity of Lectins in Mistletoe Preparations by Monoclonal Antibodies to Their A-Subunits - Tonevitsky, Alexander G.; Agapov, Igor; Temiakov, Dimitry; Moisenovichc, Mikhail; Maluchenko, Natalya; Solopovaa, Olga; Würzner, Gudrun; Pfueller, Uwe (Arzneimittelforschung, 1999)
Monoclonal antibodies (monAbs) displaying diverse affinity to native and recombinant mistle- toe lectins A-chains (ML I-A, ML II-A, ML III-A and rML-A) have been obtained. In ac- cordance to specificity of monAb they have been classified into three groups:1. monAb against MLI-A and MLII-A,2. monAb against MLII-A and MLIII-A,3. monAb against A-subunits of MLI, MLII and MLIII.The results indicate that antigen determinants of mistletoe lectins recognized by monAb MNA4, MNA9 and MTC12 do not contain any carbohydrates. Assay of lectins in mistletoe preparations was based on enzyme-linked lectin assay to meet the requirements given in the guidelines for drug tests. In this paper a sandwich ELISA test-system is described which allows to identify each of three ML-toxins. With the detection limits below 3 ng/ml and a linear measuring range of 3−30 ng/ml, dosages of mistletoe lectins in therapeutic range can be as- sayed. The problems in mistletoe lectins determination, structural differences and nature of heterogeneity of this proteins are discussed.
Keywords: Lektinol®; Mistletoe lectins, enzyme-linked immunosorbent assay; monoclonal antibodies; Ribosome-inactivating protein